Moving forward: The Japanese kelp Undaria pinnatifida (harvey) suringar, 1873 expands in Northern Patagonia, Argentina - Pereyra, Patricio Javier (2014)
Increasingly, global trade and human movement have been transporting species between regions. Undaria pinnatifida (Harvey) Suringar, 1873, a macroalgae native to Korea and Japan, has been transported and became established in several temperate regions of the world. Here we report its presence in a new coastal area of northern Patagonia, Argentina, with a description of the sporophytes.